Effect of season on the biochemical characteristics of donkey (Equus asinus) semen* - ROY, A K; YADAV, M P; SENGAR, O P S (The Indian Journal of Animal Sciences, 2014)
The biochemical characteristics of donkey semen were studied during summer, autumn and winter. The mean concentration of glucose in the seminal plasma was significantly higher (P